IMPROVING SOCIAL SCIENCES LEARNING OUTCOMES THROUGH ONLINE LEARNING AT SDN 005 KEMPAS JAYA - Syafri Efnedi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this study was to improve social studies learning outcomes through online learning. This research was a collaborative classroom action research (CAR) in which teachers and researchers worked together in order to improve the learning outcomes of fourth grade students at SDN 005 Kempas Jaya, Kecamatan Kempas, Kabupaten Indragiri Hilir. The results of this study showed that the percentage of teachers’ activities in online learning in Cycle I meeting 1 was 76% and it increased in meeting II to 76.16%. Meanwhile, in Cycle II, the percentage of activities at meeting I was 80.33% and it increased to 85.5% at meeting II. It was observed that the teacher's activities carried out in online learning on social studies subjects increased the students’social studies learning outcome. It was seen from the average initial score (before implementing online learning) shwoed only 56.53; at the end of Cycle I, the average score of student learning outcomes increased to 65.77 with an increase of 9.24 points. It was found that the students were still not familiar with the impekemntation of online learning in Cycle I since this learning provided more opportunities for students to be able to use technology, especially smartphones, as a learning tool. Meanwhile, at the end of the test in Cyle II, the average score of students’ learning outcomes increased to 69.03 with an increase of 12.5 points. There has been an increase in students’ learning outcomes by implementing online learning.